Internal Conflictsare The Biggest Deals For An Introverted Person in Paulo Coelho’s The Zahir - HARYO PARIKESIT H P (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
This study deals with revealing The Intern Conflict are The biggest deal for an introverted person. The problems discussed in this study are related to reveal the characterization of The Main Character which is an introverted person, this research also reveals that the internal conflicts are been the biggest deal for an introverted person as represented by The Major Character “I” a 58 years old man and last but not least this research also reveals the way to solve his internal conflicts. The internal conflicts include, introverted thinkings, introverted feelings, introverted intuitions, and introverted sensations.  So this journal will explain more about those internal conflicts that The Major character had to face and reveals that those internal conflicts are been the biggest deal for him. He struggles to overcome and deal those internal conflicts. This research also provides the solution of those internal conflicts. The Major Character “I” ‘s life is dominated by his darked past and bad memories with people surround him. His wife “Esther” has important role of his self-conception. He always performs as “good” person to others including his wife and his existence in the society. “I” also has a happy friendship with Mikhail a person whom at first leads him thinking that Mikhail is the one whom his wife left him for but at the end Mikhail will bring him to find his wife. In the mid of his journey to find his wife, she met Marie, the woman who also help him to stay cool and calm to find his wife even though at the end she loved him. He has been an introverted person for years and the main reason why made him an introverted person is his darked memories and childhood. The gone of his wife made such internal conflicts in his mind and heart. “I” is an introverted person so he always kept those all inside. He nailed it. this thesis will explain more about those internal conflicts that The Major character had to face and reveals that those internal conflicts are been the biggest deal for him. He struggles to overcome and deal those internal conflicts. This research also provides the solution of those internal conflicts that The Major Character “I” should did to overcome or decrease his internal conflicts.